Influência da adição de nióbio sobre a usinabilidade de ferro fundido cinzento perlítico na operação de torneamento - Bárbara Cristina Mendanha Reis (2021)
The attempt to reduce weight, by reducing the cross sections of components, linked to an increasing demand for greater thermal efficiency, requires more efforts in the development of gray cast iron. Therefore, metallurgical interferences, through the addition of elements or by the reformulation of chemical compositions, and thermal treatments have been conducted to achieve a more appropriate balance between properties. Niobium is a carbide forming and stabilizing element in gray cast iron alloys and its addition can contribute to the modification of its microstructural characteristics, mechanical and thermal properties, and consequently, impact its machinability. This work aimed to evaluate the impact of adding 0.23% niobium by weight on a pearlitic gray cast iron (FC 0.23% Nb). Its machinability was compared to material with the same base composition with low niobium content (FC 0.02% Nb) in turning using different cutting speeds, feed rates and carbide inserts with and without chipbreaker geometries. Microstructural characteristics, Brinell and Vickers hardness, limit of tensile strength and thermal diffusivity, components of the machining forces, chip temperature and roughness of the specimens were evaluated. The cast alloys were classified as hypoeutectic gray cast irons with a perlite-ferritic matrix. FC 0.23% Nb samples showed higher volumetric fraction of free ferrite, branched and non-polyhedral niobium carbides. The higher content of niobium contributed to the refinement of graphite and decreased the interlayer distance of the pearlite, however, it was indifferent to cell density. Samples with a higher niobium content did not show significant changes in their mechanical and thermal properties. The cutting of the 0.23% Nb FC samples, combined with the tool without chip breaking and higher feed rate, provided greater machining forces. When chip-breaking geometry was used together at the lowest cutting speeds and feed rates, regardless of the niobium content of the samples, the chip temperatures were reduced. The cut of the 0.23% Nb FC samples with chipbreaker geometry and lower advance promoted the lowest Ra values. Only the advance caused significant changes in Rt.